Profile of Allergic Rhinitis and its Association with Chronic Suppurative Otitis Media - Afriana, Aziza; Syabriansyah, Syabriansyah; Dita, Diah Ayu Aguspa (Muhammadiyah Medical Journal, 2023)
Background: Allergic rhinitis is a growing global public health issue. Complications of allergic rhinitis include sinusitis, nasal polyps, bronchial asthma, and otitis media. Allergic rhinitis causes Eustachian tube dysfunction, which leads to chronic otitis media threefold more often. Chronic suppurative otitis media (CSOM) is marked by persistent tympanic membrane perforation and recurrent or persistent mucopurulent otorrhea. Purposes: This study is to determine the relationship between allergic rhinitis and the prevalence of chronic suppurative otitis media in Dr. M Yunus Bengkulu Hospital during 2019-2020. Methods: This was an observational cross-sectional study. This research is an observational analytical study with a cross-sectional approach. Thirty-three respondents were taken using a simple random sampling method. The SFAR (Score for Allergic Rhinitis) questionnaire was used in this study. Medical record data were used to collect CSOM information. Result: Seventy-five percent of respondents with allergic rhinitis also had chronic suppurative otitis media, while the prevalence of non-chronic suppurative otitis media was 25 percent. The p-value for the chi-square test was 0.031. Conclusion: For 2019-2020, there is a relationship between allergic rhinitis and the prevalence of chronic suppurative otitis media (CSOM) at Dr. M. Yunus Bengkulu Hospital.